Comparative Neurology of Circadian Photoreception: The Retinohypothalamic Tract (RHT) in Sighted and Naturally Blind Mammals - Hannibal, Jens (Frontiers in Neuroscience, 2021)
The mammalian eye contains two systems for light perception: an image detecting system constituted primarily of the classical photoreceptors, rods and cones, and a non-image forming system (NIF) constituted of a small group of intrinsically photosensitive retinal ganglion cells driven by melanopsin (mRGCs). The mRGCs receive input from the outer retina and NIF mediates light entrainment of circadian rhythms, masking behavior, light induced inhibition of nocturnal melatonin secretion, pupillary reflex (PLR), and affect the sleep/wake cycle. This review focuses on the mammalian NIF and its anatomy in the eye as well as its neuronal projection to the brain. This pathway is known as the retinohypothalamic tract (RHT). The development and functions of the NIF as well as the knowledge gained from studying gene modified mice is highlighted. Furthermore, the similarities of the NIF between sighted (nocturnal and diurnal rodent species, monkeys, humans) and naturally blind mammals (blind mole rats Spalax ehrenbergi and the Iberian mole, Talpa occidentalis) are discussed in relation to a changing world where increasing exposure to artificial light at night (ALAN) is becoming a challenge for humans and animals in the modern society.